Pengaruh Fasilitas Kerja dan Semangat Kerja Terhadap Produktivitas Kerja Karyawan Pada PT ASDA Perkebunan Aek Buru Selatan - Liana, Sandria; Ulya, Basyarul; Srimulat, Fitri Endang (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of work facilities and work enthusiasm on employee work productivity at PT Asda Perkebunan Aek Buru Selatan. The study methodology employs quantitative analysis via data collection approaches via questionnaires. The research sample comprised 35 employees. The study's findings demonstrate that workplace amenities and employee motivation significantly influence productivity. Work facilities encompass tools, resources, and infrastructure that assist employees in performing their tasks more efficiently, hence enhancing their productivity. High work passion demonstrates a commitment to performing tasks and motivates individuals to work more efficiently. Organizations ought to prioritize work environments and enhance employee motivation to boost productivity. Work productivity pertains to the issue of the ultimate outcome, namely the quantity of results achieved in the manufacturing process. This opinion indicates that work productivity is the outcome attained